Analysis of socio-economic characteristics and physical condition of the slum environment in the inner city - Gbenga John Oladehinde (Urbanization, Sustainability and Society)
Purpose – Research on the living conditions of slum dwellers in the inner cities of developing countries has received much attention. Nevertheless, there is little empirical research on the influence of personal attributes on the poor environmental condition of the slum area. This study aims to examine the relationship between the socio-economic characteristics and the physical condition of the slum environment in the inner city of Ibadan, Nigeria. Design/methodology/approach – Data was collected through the use of questionnaire administration from a household survey of 491 slum dwellers. Systematic random sampling was used in the selection of the respondents. The study used descriptive, factor and multiple regression to analyse the data collected. Findings – The study used descriptive, factor and multiple regression to analyse the data collected. The study reveals an interplay between various socio-economic factors and environmental conditions. The results show that out of ten (10) socio economic variables that were submitted in the regression model, only eight (8) of these variables such as income, household size, occupation, level of education, age, marital status, year of residency and nativity were significant. Originality/value – The study concluded that despite the fact that the condition of the slum environment is a product of multiple interrelated factors, personal attributes also contribute to the poor environmental condition of the slum area. The study recommended that improving the socio-economic conditions of slum dwellers would lead to improved environmental conditions.